Effects of Weight Loss Induced by Eight-Week Orlistat Therapy on Maximal Work Production Capacity in Obese Females - Özçelik, O?uz; Do?an, Halil; Keleştimur, Haluk (My University, 2004)
The aim of this study was to examine the effects of weight loss induced by pharmacotherapy combined with a hypocaloric diet for a period of 8-weeks on maximal work (Wmax) production capacity and aerobic fitness in obese patients. Twelve obese females were put on an integrated energy restricted diet with orlistat supplement 3 ? 120 mg/day. Each patient performed 3 incremental ramp exercise tests using an electromagnetically braked cycle ergometer: one at onset, one at the end of 4-weeks and one at the end of the 8-weeks to determine Wmax production capacity. The first 4-week therapy period resulted in a significant reduction in total body weight (91.4 ± 3.1 kg vs. 88.2 ± 2.9 kg, P = 0.0001) and body fat mass (38.7 ± 1.9 kg vs. 37.5 ± 2.0 kg, P = 0.03). However, the weight reduction achieved during first 4-weeks was not associate with increased Wmax production capacity: 90.8 ± 5 W vs. 92.9 ± 5 W (P = 0.5). During the 8-week therapy period, further reductions in both body weight (86.0 ± 2.8 kg, P = 0.0001) and body fat mass (36.2 ± 1.8 kg, P = 0.002) were observed. Wmax production capacity increased slightly but was not statistically significant: 100.4 ± 6 W (P = 0.08). The impaired aerobic fitness of obese patients did not improve during the short-term obesity therapy despite significant decreases in body weight and fat mass. Thus, it is important to consider an aerobic exercise training program known to increase aerobic fitness and Wmax capacity in addition to short-term dieting and pharmacotherapy.
Keywords: Body mass index; Obesity; Orlistat; Weight loss